Retrospective Descriptive Study of an Intensive Care Unit at a Ugandan Regional Referral Hospital - Ttendo, Stephen S.; Was, Adam; Preston, Mark A.; Munyarugero, Emmanuel; Kerry, Vanessa B.; Firth, Paul G. (World journal of surgery, 2016)
Background: We describe delivery and outcomes of critical care at Mbarara Regional Referral Hospital, a Ugandan secondary referral hospital serving a large, widely dispersed rural population. Methods: Retrospective observational study of ICU admissions was performed from January 2008 to December 2011. Results: Of 431 admissions, 239 (55.4 %) were female, and 142 (33.2 %) were children (\18 years). The median length of stay was 2 (IQR 1–4) days, with 365 patients (85 %) staying less than 8 days. Indications for admission were surgical 49.3 % (n = 213), medical/pediatric 27.4 % (n = 118), or obstetrical/gynecological 22.3 % (n = 96). The overall mortality rate was 37.6 % (162/431) [adults 39.3 % (n = 113/287), children 33.5 % (n = 48/143), unspecified age 100 % (n = 1/1)]. Of the 162 deaths, 76 (46.9 %) occurred on the first, 20 (12.3 %) on the second, 23 (14.2 %) on the third, and 43 (26.5 %) on a subsequent day of admission. Mortality rates for common diagnoses were surgical abdomen 31.9 % (n = 29/91), trauma 45.5 % (n = 30/66), head trauma 59.6 % (n = 28/47), and poisoning 28.6 % (n = 10/35). The rate of mechanical ventilation was 49.7 % (n = 214/431). The mortality rate of ventilated patients were 73.5 % (n = 119/224). The multivariate odd ratio estimates of mortality were significant for ventilation [aOR 6.15 (95 % CI 3.83–9.87), p\0.0001] and for length of stay beyond seven days [aOR 0.37 (95 % CI 0.19–0.70), p = 0.0021], but not significant for decade of age [aOR 1.06 (95 % CI 0.94–1.20), p = 0.33], gender [aOR 0.61(95 % CI 0.38–0.99), p = 0.07], or diagnosis type [medical vs. surgical aOR 1.08 (95 % CI 0. 63–1.84), medical vs. obstetrics/gynecology aOR 0.73 (95 % CI 0.37–1.43), p = 0.49]. Conclusions: The ICU predominantly functions as an acute care unit for critically ill young patients, with most deaths occurring within the first 48 h of admission. Expansion of critical care capacity in low-income countries should be accompanied by measurement of the nature and impact of this intervention.
Keywords: Intensive Care Unit; Critical care; Hospital